Development of photodiode via the rapid melt growth (RMG) materials for energy conversion device - Nurfarina Zainal; S. J.N. Mitchell; D. W. McNeill; W. M. Jubadi (Institute of Advanced Engineering and Science, 2020)
Germanium (Ge) photodiodes were fabricated with the new RMG crucible materials that were established in this study. Results show that Ge large square patterns with size of 208 µm x 208 µm were unable to be achieved if ion implantation process was used in formation of photodiode. Delamination can be observed on all test samples during polycrystalline silicon (poly-Si) deposition at 620 oC. This result was in contrast to a previous intrinsic Ge test structure, where good formation of squares with size similar to that 208 µm x 208 µm had been successfully attained even with high annealing temperature above 938 oC. This indicates that doping through ion implantation has affected Ge film and caused delamination even at low temperature. However, good formations of Ge stripes were attained along with the ion implantation process in fabricating the photodiode. Results show that the sheet resistance of Ge stripe has significantly decreased compared to previous Ge resistors. The better resistance is due to the thicker (500 nm) Ge layer. In the case of Ge stripes with a p-i-n junction, only small fraction of test samples have shown a diode characteristic but with high leakage current. Results of I-V measurement show that a large fraction of test samples produced resistor characteristics. The high leakage current is believed due to the fact that the Ge films formed at this stage were polycrystalline in structure. Thus the grain size of Ge stripe has affected the performance. Slight changes on the I-V characteristic of single Ge can be observed when samples were tested under illumination. Therefore, it has potential to be used for future development of energy conversion device.